Albert Ellis live! - Dryden, Windy (SAGE Publications, 2003)
Ellis demonstrates the processes of his Rational Emotive Behavior Therapy through transcripts of five of his therapy sessions. The transcripts are presented twice, once simply by themselves and once accompanied by commentary by Dryden (psychotherapeutic studies, Goldsmiths College) wherein he describes the processes and principles at work.